Meaning Relations on Racism and Racial Discrimination News in the Jakarta Post - Dedy Subandowo (English Department - University of Sultan Ageng Tirtayasa, 2021)
This paper addresses meaning relations on racism and racial discrimination news in the Jakarta Post. The study highlights some issues dealing with how media texts provide an opinion concerning equality as well as racist prejudice. One of fundamental elements that must be considered in journalistic discourse is meaning relations between sentences and clauses (Fairclough, 1992). The study involves social inequality, semantic, grammatical as well as equivalence and difference relations. Considering the phenomenon of meaning-making relations in the journalistic discourse, especially dealing with racism and discrimination in Indonesia, this research examines a text published on the Jakarta Post.